METHODOLOGICAL BASIS OF USING MODERN INFORMATION TECHNOLOGIES IN PREVENTIVE MEDICINE - Serheta , Ihor (Collection of scientific papers «ΛΌГOΣ», 2023)
Among the most pressing problems of preventive medicine today are the problems of prenosological diagnostics of disorders in the state of health of a different character, a comprehensive assessment of the functional state and adaptive capacities of the organism, adequate hygiene night monitoring, that problems, which, of course, will require the use of modern information technologies [1, 2, 3]. Such a camp zoomed in on the development of methodological foundations and applied foundations of their research in the course of conducting hygienic studies [4, 5, 6, 7, 8]..